Interactions between particulate matter and bacteria during cowshed PM2.5-induced respiratory injury initiates GBP2/Caspase-11/NLRP3-mediated intracellular bacterial defense and pyroptosis - Du, Xiaohui; Ma, Zhenhua; Sun, Yize; Jia, Yunna; Zhang, Xiqing; Zhao, Cuizhu; Liang, Xiaojun; Yu, Xiuzhen; Gao, Yunhang (Frontiers in Veterinary Science, 2025)
IntroductionFine particulate matter (PM2.5) is an important factor in the induction of a variety of respiratory diseases and associated cellular damage. The composition of PM2.5 in the animal farm environments is complex, which poses a significant threat to the respiratory health of both workers and livestock, but the causative mechanisms are unclear.MethodsIn order to investigate targeted treatment options, this study focused on the role of microbial components in cowshed PM2.5-induced respiratory damage. Utilizing the common pathogenic bacteria (Pasteurella multocida) in cowshed PM2.5 as a perspective, the intrinsic connection and interaction mechanism between PM2.5 particles and bacterial components were explored through in vivo and in vitro experiments. Bacterial components can interact with PM2.5 and are important factors in the respiratory toxicity of PM2.5 in farm animal environments by scanning electron microscopy (SEM), Fourier infrared spectroscopy (FTIR) and Zeta potential measurements.ResultsWe demonstrate that Bacteria adhered to PM2.5 particles and modified the original surface functional groups characteristics, significantly enhanced toxic effects of PM2.5 on cells (including oxidative stress levels, release of inflammatory factors, etc.). Furthermore, PM2.5 particles significantly enhanced bacterial intracellular invasion, initiated the guanylate-binding protein 2 (GBP2)-mediated intracellular bacterial defense mechanism, further triggered the non-canonical NLRP3 pathway, and ultimately induced a cascade of inflammatory responses and pyroptosis. To explore therapeutic strategies, siRNA silencing of GBP2 and inhibition of NLRP3 were done; GBP2 silencing initially delayed cytotoxicity, but eventually increased the inflammatory response. However, inhibition of NLRP3 expression maintained cell viability and delayed pyroptosis, with potential as an effective solution for treatment of PM2.5-induced lung injury in farm-animal environments.ConclusionIn conclusion, the results of this study demonstrated the interaction between particulate matter and bacteria during cowshed PM2.5-induced respiratory injury and clarified the signaling mechanisms among intracellular bacteria, GBP2, NLRP3, and pyroptosis. These findings provide a theoretical basis for developing therapeutic strategies against PM2.5-related respiratory diseases in farm-animal environments.